2014
DOI: 10.1073/pnas.1418204111
|View full text |Cite|
|
Sign up to set email alerts
|

Days to heading 7 , a major quantitative locus determining photoperiod sensitivity and regional adaptation in rice

Abstract: www.pnas.org PNAS |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
248
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 257 publications
(264 citation statements)
references
References 32 publications
5
248
1
4
Order By: Relevance
“…In rice, LD repression of flowering is mediated by two additional CCT domain genes: Hd2/PSEUDO-RESPONSE REGULATOR37 (OsPRR37) and Hd4/ GRAIN NUMBER, PLANT HEIGHT, AND HEADING DATE7 (Ghd7; Xue et al, 2008;Koo et al, 2013;Gao et al, 2014). OsPRR37 is orthologous to the Arabidopsis circadian clock gene PRR3/7 and is characterized by a pseudoreceiver and a CCT domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In rice, LD repression of flowering is mediated by two additional CCT domain genes: Hd2/PSEUDO-RESPONSE REGULATOR37 (OsPRR37) and Hd4/ GRAIN NUMBER, PLANT HEIGHT, AND HEADING DATE7 (Ghd7; Xue et al, 2008;Koo et al, 2013;Gao et al, 2014). OsPRR37 is orthologous to the Arabidopsis circadian clock gene PRR3/7 and is characterized by a pseudoreceiver and a CCT domain.…”
mentioning
confidence: 99%
“…OsPRR37 is orthologous to the Arabidopsis circadian clock gene PRR3/7 and is characterized by a pseudoreceiver and a CCT domain. OsPRR37 is expressed under LD and SD conditions but is only functional to repress Hd3a under LDs (Murakami et al, 2003;Koo et al, 2013;Gao et al, 2014). Interestingly, PHOTOPERIOD1 (Ppd-H1), the barley homolog of the LD repressor OsPRR37, is the major photoperiod response gene in barley and induces flowering under LDs by up-regulating HvFT1, the barley homolog of Hd3a (Turner et al, 2005).…”
mentioning
confidence: 99%
“…In this study, we found that overexpression of OsMYB1R1-VP64 increased grain yield and plant height in rice by delaying flowering time (Figs 1 and 2). Several rice flowering-related pleiotropic genes such as Hd1, Ghd7, DTH8, and DTH7 were discovered in the last 10 years [4,6,7,9]. These genes delay flowering, increase plant height, and increase grain number.…”
Section: Discussionmentioning
confidence: 99%
“…Many pleiotropic genes that function in delayed flowering along with higher yield have been investigated. Those genes have been described as Days to heading 7 (DTH7), Early heading date 2 (Ehd2), Heading date 1 (Hd1), Grain number, plant height and heading date 7 (Ghd7), and Days to heading 8 (DTH8) [4,[6][7][8][9]. Under natural long-day (NLD) conditions, Ghd7 delays flowering by about 20 days and causes yield increases of 50%, and both Hd1 and DTH8 delay flowering time with increasing grain number per spike.…”
mentioning
confidence: 99%
“…The major locus days to heading 7 (DTH7) controls photoperiod sensitivity and affects grain yield in rice. DTH7 encodes a pseudo-response regulator protein whose expression is regulated by photoperiod, for example, under long days, DTH7 acts downstream of the photoreceptor phytochrome B to repress the expression of Ehd1, which is an up-regulator of the florigen genes Hd3 and RFT1, thereby leading to delayed flowering (Gao et al 2014). The combination of DTH7 with grain number, plant height, heading date 7 (Gdh7), and DHT8 haplotypes relates to flowering time and grain yield in rice cultivars across day lengths.…”
mentioning
confidence: 99%